Endovascular thrombectomy in acute ischemic stroke patients with COVID-19: prevalence, demographics, and outcomes. (28th September 2020) - de Havenon, Adam; Yaghi, Shadi; Mistry, Eva A; Delic, Alen; Hohmann, Samuel; Shippey, Ernie; Stulberg, Eric; Tirschwell, David; Frontera, Jennifer A; Petersen, Nils H; Anadani, Mohammad
Abstract : Background: We aimed to compare the outcome of acute ischemic stroke (AIS) patients who received endovascular thrombectomy (EVT) with confirmed COVID-19 to those without. Methods: We performed a retrospective analysis using the Vizient Clinical Data Base and included hospital discharges from April 1 to July 31 2020 with ICD-10 codes for AIS and EVT. The primary outcome was in-hospital death and the secondary outcome was favorable discharge, defined as discharge home or to acute rehabilitation. We compared patients with laboratory-confirmed COVID-19 to those without. As a sensitivity analysis, we compared COVID-19 AIS patients who did not undergo EVT to those who did, to balance potential adverse events inherent to COVID-19 infection. Results: We identified 3165 AIS patients who received EVT during April to July 2020, in which COVID-19 was confirmed in 104 (3.3%). Comorbid COVID-19 infection was associated with younger age, male sex, diabetes, black race, Hispanic ethnicity, intubation, acute coronary syndrome, acute renal failure, and longer hospital and intensive care unit length of stay. The rate of in-hospital death was 12.4% without COVID-19 vs 29.8% with COVID-19 (P<0.001). In mixed-effects logistic regression that accounted for patient clustering by hospital, comorbid COVID-19 increased the odds of in-hospital death over four-fold (OR 4.48, 95% CI 3.02 to 6.165). Comorbid COVID-19 was also associated with lower odds of a favorable discharge (OR 0.43, 95% CI 0.30 to 0.61). In the sensitivity analysis, comparing AIS patients with COVID-19 who did not undergo EVT (n=2139) to the AIS EVT patients with COVID-19, there was no difference in the rate of in-hospital death (30.6% vs 29.8%, P=0.868), and AIS EVT patients had a higher rate of favorable discharge (32.4% vs 47.1%, P=0.002). Conclusion: In AIS patients treated with EVT, comorbid COVID-19 infection was associated with in-hospital death and a lower odds of favorable discharge compared with patients without COVID-19, but not compared with AIS patients with COVID-19 who did not undergo EVT. AIS EVT patients with COVID-19 were younger, more likely to be male, have systemic complications, and almost twice as likely to be black and over three times as likely to be Hispanic.